Metastatic Neuroblastoma Masquerading as Ewing’s Sarcoma on X-ray: An Imaging Puzzle in Pediatric Oncology - Mukesh Kumar; Jitendra Sharma; Radha Sarawagi; Varun Tej; Ishudeep Kaur; Dega Vamsikrishna (Journal of Orthopaedic Case Reports)
Introduction: Neuroblastoma is an embryonic tumor of the peripheral sympathetic nervous system. It is the most common extracranial solid tumor of childhood and accounts for up to 15% of all pediatric cancer fatalities. The manifestation of neuroblastoma is variable depending on the location of the tumor and the presence or absence of paraneoplastic syndromes. Neuroblastoma has a great propensity to metastasize to multiple organs. The most common site of metastasis is the bone and bone marrow. Ewing sarcoma is a rare small round blue cell tumor originating from neuroectoderm. It is the most common primary bone tumor of adolescents. The most common anatomical sites of involvement include the pelvis, axial skeleton, and femur; however, Ewing sarcoma can occur in almost every bone or soft tissue. Here we report a primary expansile bony lesion in the left femur mimicking Ewing’s sarcoma which on extensive workup was diagnosed as metastasis of adrenal neuroblastoma. This is the first report of this kind in the literature. Case Report: A 3-year-old female child presented with complaints of swelling in the left thigh for 2 months. She did not have any abdominal complaints. Her initial X-ray of the thigh revealed increased density and thickness of soft tissue in the mid and distal thigh and laminated periosteal reaction with focal areas of sunburst appearance in the left femoral diaphysis region. Ultrasound (USG) of the thigh confirmed the findings of the X-ray and a provisional diagnosis of Ewing’s sarcoma was considered. During the routine workup, an USG abdomen was done which revealed an infiltrating retroperitoneal mass crossing the midline, encasing the aorta and its branches. Contrast-enhanced computed tomography of the abdomen confirmed the sonographic findings that a heterogeneously enhancing mass encasing and displacing the abdominal aorta and the left kidney was noted. The left adrenal gland was not separately visualized. Based on these findings, the primary diagnosis of metastatic neuroblastoma bony metastasis was made. Histopathology and immuno-histochemistry of the left suprarenal mass confirmed the diagnosis of neuroblastoma. Conclusion: Neuroblastoma can primarily present with musculoskeletal symptoms such as expansile metastatic bony lesions or pathological fractures and should be considered in the differential diagnosis.